Determinação de gordura, proteína, cobre, ferro, manganês, zinco e contagem de células somáticas no leite de vacas com mastite subclínica - Domingues, Paulo Francisco; Langoni, Helio; Padovani, Carlos Roberto; Gonzales, Jorge A. H.; Fregonesi, Otavio B. (Semina: Ciências Agrárias, 2004)
The purpose of this paper was to investigate the relationship between of bovine mastitis and the nutrients concentration in milk. Seventy-two Holstein cows were divided into 2 groups: G1 - clinically healthy cows (n = 36) and G2 - subclinical mastitis cows (n = 36). Both groups of animals were subjected to the California Mastitis Test - CMT, the somatic cell counting, and the microbiological examination. The concentrations of fat, matter protein, copper, iron, manganese and zinc in the milk sample were determined. The recorded data were statistically analyzed and presented the following means and standard-deviations, according to groups 1 and 2: fat (%) 1.251 ± 0.676 and 1.662 ± 1.166 (p > 0.05); protein (%) 3.373 ± 0.428 and 3.411 ± 0.348 (p > 0.05); somatic cell counting (after logarithmic basis) 1.694 ± 0.632 and 2.909 ± 0.424 (p < 0.0001); copper (ppm) 0.043 ± 0.015 and 0.047 ± 0.019 (p > 0.05); iron (ppm) 0.159 ± 0.047 and 0.191 ± 0.063 (p < 0.05); manganese (ppm) 0.040 ± 0.010 and 0.036 ± 0.010 (p > 0.05) and zinc (ppm) 3.938 ± 1.221 and 3.658 ± 1.212 (p > 0.05). It was concluded that there were significant differences in the levels of SCC and iron between the two groups of animals.